The Effect of Service Quality on Customer Saving Intention Mediated by Security Perception and Religiosity as Moderating Variables - Gitta Safira; Martaleni Martaleni; Umi Muawanah (Celebes Scholar pg, 2026)
This study aims to empirically examine the influence of service quality on the saving intention of Islamic bank customers. It further investigates the mediating role of security perception in this relationship and analyzes the moderating effect of religiosity on the link between service quality and saving intention. This research method uses a quantitative approach through a survey. Primary data were collected via questionnaires from priority customers of Bank Syariah Indonesia using a purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) to test the direct relationship and mediation effects of perceived security and religiosity as hypothesized in the research framework. The findings confirm that service quality directly enhances saving intention at BSI. Crucially, security perception acts as a significant partial mediator, meaning service quality builds trust and a sense of security, which in turn strengthens saving intention. Furthermore, religiosity positively moderates this relationship; customers with higher religiosity demonstrate a stronger link between perceived service quality and their intention to save, affirming the value of Sharia-compliance. This research enriches the marketing and Islamic finance literature by providing a validated model that incorporates mediation and moderation. It moves beyond direct-effect models, demonstrating how service quality translates into saving intention through the critical psychological mechanism of security perception. This study acknowledges several limitations. The geographic focus on a single BSI branch in Jakarta restricts the generalizability of the findings to other regions with different cultural or economic contexts.